2014
DOI: 10.1021/ja5055143
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Insertion into Metal Carbon Bonds: Formation of Methylperoxo Pd(II) and Pt(II) Complexes via Photogenerated Dinuclear Intermediates

Abstract: Platinum(II) and palladium(II) complexes [M(CH3)(L)]SbF6 with substituted terpyridine ligands L undergo light-driven oxygen insertion reactions into metal methyl bonds resulting in methylperoxo complexes [M(OOCH3)(L)]SbF6. The oxygen insertion reactions occur readily for complexes with methyl ligands that are activated due to steric interaction with substituents (NH2, NHMe or CH3) at the 6,6″-positions on the terpyridine ligand. All complexes exhibit attractive intermolecular π···π or M···M interactions in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 81 publications
2
57
0
1
Order By: Relevance
“…These results favour a monometallic pathway, in contrast to previous suggestions that photoexcitation and oxygen quenching take place through a bimetallic mechanism involving two complex molecules in the form of a dimer. 13 Our calculations show that once 3 A is formed, coordination of dioxygen takes place without the need for a second complex. We confirmed this conclusion through calculations on the bimolecular mechanism reported in the ESI.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…These results favour a monometallic pathway, in contrast to previous suggestions that photoexcitation and oxygen quenching take place through a bimetallic mechanism involving two complex molecules in the form of a dimer. 13 Our calculations show that once 3 A is formed, coordination of dioxygen takes place without the need for a second complex. We confirmed this conclusion through calculations on the bimolecular mechanism reported in the ESI.…”
Section: Resultsmentioning
confidence: 75%
“…Recently, Britovsek et al 13 15 and Goldberg et al 16 18 reported that platinum methyl complexes can insert dioxygen to give the methylperoxo product. One of the remarkable aspects of the reaction reported by Britovsek was the strong dependence of the insertion on the substituents in the 6 and 6′ positions of the terpyridine ligand ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…图式 14 光催化偶联放氢合成芳基唑类化合物 Scheme 14 Photocatalytic hydrogen-evolution coupling synthesis of aryl azoles 咪唑并吡啶是重要的稠合双环 5~6 元杂环结构, 在药物化学中被广泛应用 [50,51] . 雷爱文课题组 [52] 由于金属与氧元素的 HOMO 和 LUMO 之间较高的 能垒, C-H 官能化形成 C-O 键在金属催化中受到的关 注较少 [59] . 近年来, 过渡金属催化的羧酸的氧化脱氢交 叉偶联技术推进了 C-O 键的构建, 但必须加入氧化剂 和牺牲剂限制了反应的适用性 [60,61] .…”
Section: 活化 Sp 3 -碳的交叉偶联放氢反应unclassified
“…Similar 6,6′′‐substituted terpyridines containing weaker pendent H‐bond donor amine groups have been reported previously with R=NH 2 , NH(CH 3 ), NH(C 2 H 5 ) . However, their associated coordination chemistry is limited to three reports using Pt and Pd ,…”
Section: Figurementioning
confidence: 99%